Karakteristik Fisis dan Mekanis Papan Semen Bambu Hitam (Gigantochloa Atroviolacea Widjaja) dengan Dua Ukuran Partikel Physical and Mechanical Characteristics of Cement Board Bamboo Hitam (Gigantochloa atroviolacea Widjaja) Using Two Particle Sizes. - Rini Armaya; Evalina Herawati; Tito Sucipto (Program studi Kehutanan USU, 2013)
Cement boards was made ​​from bamboo hitam (Gigantochloa atroviolacea Wdjaja) using two particle sizes of 20 mesh and 40 mesh. The difference in particle size thought to affect the quality of the resulting cement board. The purpose of this study was to evaluate the physical and mechanical properties of cement board bamboo hitam using two particle sizes.Boards were made ​​with size 25 cm x 25 cm x 1 cm with density of 1.2 gr/cm3 of two different particle size of 20 mesh and 40 mesh and each made ​​in three replications. Cement board was made with ratio of particles, cement and water in 1:3:2 and the addition of MgCl2 catalyst was 5%. In general, physical properties of cement board had completed the standard JIS A 5417-1992, both cement board particle size 20 mesh and 40 mesh. Physical properties of cement board using particle size of 40 mesh better than cement board using particle size of 20 mesh. MOR value of cement board using particle size of 20 mesh had met standard while the value of MOE did not complete the standard. Internal bond and screw holding strenght did not require in standard JIS A 5417-1992. Cement board using particle size of 20 mesh had better mechanical properties than cement board using particle size of 40 mesh. Keywords: bamboo hitam, particle size, cement board, physical properties, mechanical properties